PENGARUH TINGKAT PENDIDIKAN, KETERAMPILAN KERJA, DAN SIKAP KERJA TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) KOTA PADANG - Vivi Nila Sari; Marta Widian Sari; Jepri Apriyan (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2019)
This research aims to find out how big the influence of educational level, job skills, Work Attitudes and Employee Performance Against PDAM Padang city. This research consists of three Independent Variables, namely educational level, job skills, and Work attitude of the dependent Variable and one Employee Performance. Methods of analysis used was Multiple regression Analysis. Method of data collection in this research is to use the Questionnaires filled by respondents are PDAM employees Padang City.The results of the regression analysis in this research indicate that: 1) level of education a positive and significant effect on performance of employees, 2). Job skills and significant positive effect on performance of employees, 3) Employee Attitude. a positive and significant effect on performance of employees, 4). The level of education, job skills, and a working Attitude together positive and significant effect on performance of employees. the coefficient of determination shows the value of 0.775 this case showed that the level of education, job skills and work attitudes contribute to affect the performance of the employees of 77.5% and the remaining 22.5% influenced other variable not examined.